2016
DOI: 10.1186/s12885-016-2444-5
|View full text |Cite
|
Sign up to set email alerts
|

Survival rates of cancer patients with and without rheumatic disease: a retrospective cohort analysis

Abstract: BackgroundTo compare the outcomes of gastric, colon, lung, and breast cancer patients with and without rheumatic diseases (RD).MethodsThis retrospective study compared the cancer survival rates of a cohort of 122 cancer patients with rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), dermatomyositis/polymyositis (DM/PM), or systemic sclerosis with that of a cohort of 366 age-, sex-, and, cancer type-matched patients without RD who received medical care from 2000 to 2014. Staging, comorbidities, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 34 publications
2
30
1
Order By: Relevance
“…24 In a recent retrospective study on 122 colon, gastric, lung, and BC patients with several SRDs including RA, dermatomyositis/ polymyositis (DM/PM), SLE, SSc, patients with RA and DM/PM were found to be associated with higher mortality in patients with lung cancer or BC. 25 In another study from Sweden on 1,411,163 cancer patients, patients with RA were noted to have worse prognosis, with hazard ratios of 1.29 and 1.31 for cause-specific and overall survival, respectively, compared to all cancer patients without RA. 26 However, our study did not disclose any significant difference in terms of five-year overall survival and diseasefree survival between RA patients and patients without SRDs.…”
Section: Discussionmentioning
confidence: 97%
“…24 In a recent retrospective study on 122 colon, gastric, lung, and BC patients with several SRDs including RA, dermatomyositis/ polymyositis (DM/PM), SLE, SSc, patients with RA and DM/PM were found to be associated with higher mortality in patients with lung cancer or BC. 25 In another study from Sweden on 1,411,163 cancer patients, patients with RA were noted to have worse prognosis, with hazard ratios of 1.29 and 1.31 for cause-specific and overall survival, respectively, compared to all cancer patients without RA. 26 However, our study did not disclose any significant difference in terms of five-year overall survival and diseasefree survival between RA patients and patients without SRDs.…”
Section: Discussionmentioning
confidence: 97%
“…However, the negative association between RA and breast cancer was described in studies conducted before mammographic screening was mainstay 34 35. Moreover, since the assessment of RA risk after breast cancer is, by definition, an assessment among breast cancer survivors, we cannot exclude that breast cancer among would-be patients with RA could have a worse prognosis irrespective of cancer stage 36 37…”
Section: Discussionmentioning
confidence: 98%
“…Thus, the endogenous C5a in the reaction site acted on both cancer cells and the cancer microenvironment, synergistically promoting cancer. The cancer promotion by the Arthus reaction suggests that C5a generation may be an underlying mechanism for the poor prognosis of the cancer patients with autoimmune diseases (24), particularly patients with C5aR-positive cancers. The promotion of lung nodule formation of intravenously injected C5aR-positive cancer cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune diseases are caused by immune complex-induced activation of the complement system and subsequent inflammation, both of which injure tissues (1). Recent studies have revealed an association between autoimmune diseases, including rheumatoid arthritis and thyroiditis, and worse survival in patients with lung, breast, or thyroid cancers (24); however, the underlying mechanism is still unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation